Pengaruh Kompetensi dan Kecerdasan Emosional Terhadap Kinerja Karyawan Si Doi Hotel dan Restaurant Legian - Karmandita, I Gusti Ngurah; Subudi, Made (E-Jurnal Manajemen, 2014)
This study aims to determine the effect of competence, and emotional intelligence on the performance of the employees either simultaneously or partially. The study was conducted at Si Doi Hotel and Restaurant in Legian with using employees as respondents of the study. Data collected through interviews, observations, and questionnaires. The data analysis technique used is multiple linear regression to determine the effect of variables simultaneously and partially emotional intelligence competencies and the performance of employees. Based on the results of analysis show that simultaneous variables and emotional intelligence competencies have a significant effect on employee performance. Partially variables competencies and emotional intelligence significant positive effect on employee performance Si Doi Hotel and Restaurant, Legian.
Keywords: : performance, competency, emotional intelligence